164k views
1 vote
What is the result of subtracting the second equation from the first?

-2x + y = 0
-73 + 3y = 2

User Berezh
by
6.1k points

2 Answers

7 votes
-2x + y = 0 (equation1)
-73 + 3y = 2 (equation 2)
First of all, rearrange and simplify equation so they’re in the format of y= ax + b.

Equation 1
-2x + y = 0
y = 2x + 0
y = 2x

Equation2:
-73+3y=2
3y = 2 + 73
3y = 75
3y/3 = 75/3
y= 25
Subtract second equation from first:)
y= 2x - 25
Hope this helped :)
User Lesque
by
5.7k points
1 vote

Answer:

The result is 2x + 2y - 73 = 2.

User Wez Sie Tato
by
4.8k points